In vivo anti-tumor effect of hybrid vaccine of dendritic cells and esophageal carcinoma cells on esophageal carcinoma cell line 109 in mice with severe combined immune deficiency - Guo, Guang-Hua; Chen, Su-Zuan; Yu, Jing; Zhang, Juan; Luo, Li-Li; Xie, Li-Hua; Su, Zhong-Jing; Dong, Hong-Mei; Xu, Hong; Wu, Li-Biao (World journal of gastroenterology : WJG, 2008)
AIM： To develop a fusion vaccine of esophageal carcinoma cells and dendritic cells （DC） and observe its protective and therapeutic effect against esophageal carcinoma cell line 109 （EC109）. METHODS： The fusion vaccine was produced by fusing traditional polyethyleneglycol （PEG）, inducing cytokine, sorting CD34＋ magnetic microbead marker and magnetic cell system （MACS）. The liver, spleen and lung were pathologically tested after injection of the fusion vaccine. To study the therapeutic and protective effect of the fusion vaccine against tumor EC109, mice were divided immune group and therapeutic group. The immune group was divided into P, E, D and ED subgroups, immunized by phosphate buffered solution （PBS）, inactivated EC109, DC and the fusion vaccine respectively, and attacked by EC109 cells. The tumor size, weight, latent period and mouse survival period were recorded and statistically analyzed. The therapeutic group was divided into four subgroups： P, inactivated EC109, D and ED subgroups, which were attacked by EC109 and then treated with PBS, inactivated EC109, DC, and EC109-DC respectively. Pathology and flow cytometry were also used to study the therapeutic effect of the fusion vaccine against EC109 cells. RESULTS： Flow cytometry showed that the expression of folate receptor （FR）, EC109 （C）, Des （D） in human nasopharyngeal carcinoma cell line （HNE1） （B） was 78.21%, 89.50%, and 0.18%, respectively. The fusion cells （C） were highly expressed. No tumor was found in the spleen, lung and liver after injection of the fusion vaccine. Human IgG was tested in peripheral blood lymphocytes （PBL）. In the immune group, the latent period was longer in EC109-DC subgroup than in other subgroups, while the tumor size and weight were also smaller than those in ED subgroup. In the therapeutic group, the tumor size and weight were smaller in ED subgroup than in P, inactivated EC109 and DC subgroups. CONCLUSION： Fusion cells are highly expressed not only in FR but also in CD80. The fusion vaccine has a distinctive protective effect against tumor EC109 and can inhibit the growth of tumor in mice, and its immune protection against tumor attack is more significant.